2012
DOI: 10.1007/s10641-012-0035-0
|View full text |Cite
|
Sign up to set email alerts
|

Influences of low-head dams on the fish assemblages in the headwater streams of the Qingyi watershed, China

Abstract: The influences of low-head dams on the fish assemblages were examined in this study, using fish data collected in six treatment and five reference sites at three low-head dams in the headwater streams of the Qingyi watershed, China. Comparing with those in the reference sites, local habitat variables were significantly altered by low-head dams in the treatment sites, involving wider channel (only in the impoundment area), deeper water and slower flow. Fish species richness varied significantly across seasons, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 47 publications
(82 reference statements)
1
36
0
2
Order By: Relevance
“…Many ecosystem functions are modified by dams altered flow regime. Rivers lose the former habitat and landscape traits, and present some variations in current velocity, water temperature, substrate and food‐chain (Domingues & Galvao, ; Yan, Wang, Zhu, Chu, & Chen, ). There are more than 10,000 dams in the Pearl River basin (Tan et al, ), and there are 22 large sluices and 2,550 medium and small sluices in the Pearl River Delta (Li et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Many ecosystem functions are modified by dams altered flow regime. Rivers lose the former habitat and landscape traits, and present some variations in current velocity, water temperature, substrate and food‐chain (Domingues & Galvao, ; Yan, Wang, Zhu, Chu, & Chen, ). There are more than 10,000 dams in the Pearl River basin (Tan et al, ), and there are 22 large sluices and 2,550 medium and small sluices in the Pearl River Delta (Li et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Lowhead dams in the Neosho also influence spatial patterns of fish assemblages . Porto et al (1999) and Cumming (2004) showed that fish species richness declined immediately upstream from lowhead dams in Lake Ontario streams and Wisconsin streams, respectively, and Yan et al (2012) found lower fish abundances in the impounded areas upstream from lowhead dams in the Qingyi watershed, China. Dean et al (2002) demonstrated consequences of Neosho River lowhead dams on unionid species richness and evenness.…”
Section: Discussionmentioning
confidence: 99%
“…Regretfully, to our knowledge, reports that relate stream fish assemblages to different environmental factors from a riverscape perspective are quite rare in China, where stream fishes are being severely endangered due to many anthropogenic disturbances, such as dam construction, urbanization, agriculture production, industrial release and water pollution (Fu et al 2003;Kang et al 2009;Yan et al 2013). In this study, based on the data collected in 91 sampling sites within first-order through third-order streams of the Xin'an basin, China, we examined the spatial variation in fish species richness and assemblage structures and assessed how fish assemblages related to local habitat, tributary spatial position and land use/cover within this basin.…”
Section: Introductionmentioning
confidence: 99%